Phytotherapy for Bacterial Vaginosis with Piper Betle: from Mechanism to Safety - Satria Bintang Samudra; Prawesty Diah Utami; Grissabel Bethrin Jiantoro; Jessica Euodia Adidharma; Rayhan Ali Fadli (Publication Department, Universitas Warmadewa, 2026)
Background: Bacterial vaginosis (BV) is a prevalent vaginal dysbiosis characterized by depletion of Lactobacillus and overgrowth of anaerobic bacteria, commonly including Gardnerella vaginalis. Clinical management is complicated by high recurrence rates, which are closely linked to polymicrobial biofilm persistence and the limited microbiome selectivity of conventional antimicrobials. This narrative review aimed to synthesize current evidence on the phytotherapeutic potential of Piper betle in BV, focusing on antimicrobial and anti-biofilm mechanisms, modulation of vaginal microbiome ecology, and safety and standardization considerations relevant to translational development and recurrence prevention. Methods: An exploratory literature search (2015–2025) was conducted using PubMed/MEDLINE, ScienceDirect, and Google Scholar, complemented by manual reference screening, and last searched on 30 September 2025. Results: Findings across in vitro studies, observational reports, and mechanistic literature indicate that P. betle extracts and key phenolic constituents, particularly hydroxychavicol and eugenol, exhibit antibacterial activity against BV-associated taxa and anti-virulence effects consistent with biofilm weakening and interference with quorum-sensing–regulated behaviors. Importantly, several studies suggest comparatively limited inhibitory effects on Lactobacillus spp., supporting the plausibility of a microbiome-sparing profile that may facilitate restoration of vaginal eubiosis. Nevertheless, the evidence base is constrained by heterogeneous methodologies, predominance of preclinical models, and substantial variability in phytochemical composition across preparations. Conclusion: Overall, P. betle emerges as a biologically plausible adjunctive or preventive candidate for preventing BV recurrence, warranting standardized formulations, marker-based quality control, and rigorous clinical evaluation with recurrence-focused endpoints.